Correction: Evaluation of a parasite-density based pooled targeted amplicon deep sequencing (TADS) method for molecular surveillance of Plasmodium falciparum drug resistance genes in Haiti. - Swarnali Louha; Camelia Herman; Mansi Gupta; Dhruviben Patel; Julia Kelley; Je-Hoon M Oh; Janani Guru; Jean F Lemoine; Michelle A Chang; Udhayakumar Venkatachalam; Eric Rogier; Eldin Talundzic (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262616.].